Much ado about nothing? The wage penalty of holding a Ph.D. degree but not a Ph.D. job position - Giuseppe Lucio Gaeta; Giuseppe Lubrano Lavadera; Francesco Pastore (Global Labor Organization (GLO), 2017)
This paper contributes to the literature on overeducation by empirically investigating the wage penalty of job-education mismatch among Ph.D. holders who completed their studies in Italy; a country where the number of new doctoral recipients has dramatically increased over recent years while personnel employed in R&D activities is still below the European average. We use cross-sectional micro-data collected in 2009 and rely on different definitions of education-job mismatch such as, overeducation, overskilling and dissatisfaction with the use of skills. We find that overeducation and skills dissatisfaction are associated with significantly lower wages but there is no wage penalty from overskilling. Furthermore, those who simultaneously report overeducation and skills dissatisfaction experience a particularly high wage penalty.
Keywords: C26; I23; I26; J13; J24; J28; 330; job-education mismatch; overeducation; overskilling; job satisfaction; wages; Ph.D. holders